2020
DOI: 10.1039/d0ra02694h
|View full text |Cite
|
Sign up to set email alerts
|

N-doped oxidized carbon dots for methanol sensing in alcoholic beverages

Abstract: Herein, we establish a new perspective towards economically viable non-toxic fluorescent probes as a potential substitute of expensive alternative for the detection of MeOH in alcoholic beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Among them, the foremost techniques for biomass-derived CDs have been the hydrothermal/solvothermal method and pyrolysis. Hydrothermal/solvothermal carbonization is predominantly used to synthesize CDs because of its low-cost, eco-friendly, and nontoxic processes ( Yang et al., 2017 ; Bogireddy et al., 2019 ; Latha et al., 2020 ; Bogireddy et al., 2020b ; Bogireddy et al., 2020a ; Anuar et al., 2021 ; Ge et al., 2021 ). In addition, water soluble carbon dots are generally made from hydrothermal and microwave techniques ( Kang et al., 2020 ).…”
Section: Synthesis Techniques For Obtaining Cdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the foremost techniques for biomass-derived CDs have been the hydrothermal/solvothermal method and pyrolysis. Hydrothermal/solvothermal carbonization is predominantly used to synthesize CDs because of its low-cost, eco-friendly, and nontoxic processes ( Yang et al., 2017 ; Bogireddy et al., 2019 ; Latha et al., 2020 ; Bogireddy et al., 2020b ; Bogireddy et al., 2020a ; Anuar et al., 2021 ; Ge et al., 2021 ). In addition, water soluble carbon dots are generally made from hydrothermal and microwave techniques ( Kang et al., 2020 ).…”
Section: Synthesis Techniques For Obtaining Cdsmentioning
confidence: 99%
“…In this scenario, several nanotechnology based detection systems have been proposed recently ( Xu et al., 2020 ). Various nanomaterials, including carbon-based and metallic nanoparticles, have provided a potential solution for these existing environmental challenges ( de Marco et al., 2019 ; Latha et al., 2020 ; Bogireddy et al., 2020a ; Long et al., 2021 ). Among them, green synthesized carbon dots have attracted attention because of their sustainability, low cost, biocompatibility, and ease of use.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, few organic uorescent probes for MeOH are reported in the literature and those that are have certain limitations. 17,[28][29][30] Different materials have also been used as MeOH uorosensors such as a supramolecular ionic material by Zhang et al, 31 a bimetallic lanthanide-organic framework by Du and co-workers, 32 and nitrogen-doped oxidized carbon dots by Latha et al 33 In most of the cases MeOH is differentiated only from EtOH but not from i PrOH. The detection is based on either an increase or decrease of the relative intensity changes between MeOH and EtOH but never in the opposite direction, that is an increase for one and a decrease for the other.…”
Section: Introductionmentioning
confidence: 99%
“…The materials like titanium dioxide, 15 dopamine-melanin dense nanoparticles, 16 ZnO nanoparticles, 17 can serve as UV shields due to their high UV absorbance. It is also reported that carbon dots (CDs) [18][19][20][21] can be used in UV shields due to their strong absorption in the UV range. 21 CDs can also interact with UV radiation producing uorescence.…”
Section: Introductionmentioning
confidence: 99%
“…In the past couple of decades, carbon dots have attracted the attention of the scientific community due to their fluorescence properties, biocompatibility, low cost, and the wide range of methods for their fabrication. 15 Carbon dots have been used in bio-imaging 16 and white LED (WLED) 17 applications, and for the identification/detection of metal ions, 18,19 adulterants, 20 contaminants, 21 bacteria, 22 and other microorganisms. Additionally, these nanostructures have also been incorporated into different polymers such as poly(methyl methacrylate) (PMMA) and polystyrene (PS), 23 polyvinyl alcohol (PVA), 24–28 and polyvinylidene fluoride (PVDF) 29–33 to create films and membranes for different applications.…”
Section: Introductionmentioning
confidence: 99%